Analisis peran guru dalam penanaman kedisiplinan belajar pada pembelajaran bahasa jawa kelas V sekolah dasar - Rifana, Fania Putri; Daryanto, Joko; Kurniawan, Sandra Bayu (Universitas Sebelas Maret, 2024)
This research conducted to analyzed the teacher’s role in instilling learning discipline in Javanese languange learning for fifth grade students. This is a qualitative descriptive research using a case study approach. The research results of this study show seven roles that must be implemented to instill learning discipline in Javanese languange. The role such as demonstrators, evaluators and educators still have subindicators that have not been fulfilled. However, teachers have fulfilled other roles, as communicators, organizers, motivators, and inspirers. A questionnaire was conducted to calculate the learning discipline of class V ini Javanese languange learning, so the conclusion was that in general the students' learning discipline was in the very good category. This is seen from each indicator, namely (1) discipline in participating in learning; (2) discipline in doing assignments; and (3) discipline in obeying rules and regulations. The implications of this research state that the teacher's role in instilling learning discipline in Javanese language learning can trigger students' disciplined learning behavior in participating in learning, doing assignments, and obeying rules and regulations.